Perovskite catalysts and uses thereof

Perovskite catalysts with platinum group metals and transition metal doping address the cost and performance challenges of traditional three-way catalysts by enhancing oxygen mobility and stability, achieving effective catalytic performance across varying air-fuel ratios and temperatures.

JP2025011165APending Publication Date: 2025-01-23RES TRIANGLE INST
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024173180
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2016-11-14
Filing Date
2024-10-02
Publication Date
2025-01-23

AI Technical Summary

Technical Problem

The increasing cost and scarcity of rare earth elements in three-way catalysts for vehicle exhaust gas treatment, coupled with the need for improved catalytic performance under varying air-fuel ratios and high-temperature conditions, necessitates the development of alternative oxygen storage materials that are cost-effective and thermally stable.

Method used

Incorporation of platinum group metals into perovskite structures, such as CaCo1-xZr xO3-δ, which enhances catalytic activity by stabilizing metals against sintering and volatilization, and promotes oxygen mobility through doping of A and B sites with transition metals, leading to improved redox properties and structural stability.

Benefits of technology

The perovskite catalysts exhibit superior redox properties and oxygen storage capacity, maintaining high catalytic activity under varying air-fuel ratios and high temperatures, offering a cost-effective alternative to traditional catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025011165000005
    Figure 2025011165000005
  • Figure 2025011165000006
    Figure 2025011165000006
  • Figure 2025011165000007
    Figure 2025011165000007
Patent Text Reader

Abstract

To provide perovskite catalysts that can be used as automotive oxygen storage materials such as three-way catalysts and are also useful for water or CO2 reduction or thermochemical energy storage.SOLUTION: The present invention provides a catalyst comprising a platinum-group metal and a perovskite having the formula CaCo1-xZrxO3-δ where x is a number defined by 0.02≤x≤0.98; and δ is a number defined by 0.0≤δ≤1.0.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application is a joint publication of "Perovskite" by Zheng et al., filed on November 14, 2016. No. 62 / 421,568 (Attorney Docket No. 1 This application claims the benefit of US Provisional Patent Application No. 2005 / 0133636, filed on May 21, 2005, and which is incorporated herein by reference in its entirety. To quote.

[0002] The present disclosure relates to perovskite catalyst materials and perovskite catalysts, including platinum group metals and perovskites. We provide perovskite catalysts. These catalysts are used as oxygen storage materials for automobiles, such as three-way catalysts. They can also be used for water or carbon dioxide reduction and for thermochemical energy storage. It is useful. [Background technology]

[0003] 2.1. Introduction Perovskite materials are ABO 3-δ where A and B are It is a cation that can have multiple valence states and is stable in octahedral and dodecahedral environments. It is fixed 1 The perovskite structure has a Goldschmidt tolerance factor (t) of 0.7. <t <1, while t is in the range

number

number

[0004] Oxygen storage material (OSM) is an The latest three-way catalyst (TWC) for vehicle exhaust gas regulation It is an essential element in the development of the latest TWC, which is deposited on stabilized γ-Al2O3. The supported bimetallic Pd-Rh catalysts were able to efficiently remove CO, hydrocarbons (HC), and NO x Detoxification of Allows conversion of the compounds CO2, H2O, and N2 10 TWC mode has three stains The engine is operated within a narrow stoichiometric range (lambda = 1) where all of the dyes reach their optimum conversion. 1 1 Delicate control of the λ value is achieved by Ce x O y Chemically assisted by Ce x O y Ce 4+ / Ce 3+ High oxygen storage capacity due to redox function It is well known that the Ce x O y is expressed as (2) and γ-A to improve catalytic performance via redox chemistry as shown in Eq. (3). Commercially incorporated into the l2O3 support. 2CeO2+CO → Ce2O3+CO2 (slightly fuel-rich, λ<1) (2) Ce2O3+1 / 2O2→2CeO2 (slightly fuel-lean, λ>1) (3)

[0005] In recent years, the family of rare earth elements, including cerium, has become increasingly expensive and unavailable. This has led to market confusion and a search for ways to reduce their concentrations in OSCs. was 12 On the other hand, the rapid increase in the automobile population and the need to convert as much as 96% of all pollutants With the stricter automobile emission regulations, the theoretical air-fuel ratio operating window has been widened to allow for TW There is a lot of interest in improving the performance of C 13 In addition, active metals (platinum group metals) Platinum group metals (PGM) and Ce x O y -Zr The TWC, which includes a carrier material (incorporating an O2-type OSM), has a fuel cut-off, i.e. engine motors that improve oxidation but expose the catalyst to high temperature (over 1000°C) lean oxidation conditions May be inactivated under low temperatures 13,14 Perovskite has not only excellent redox properties, It also has high chemical and structural stability. 15 Low cost, high abundance and availability By selecting a transition metal with excellent redox properties as well as good thermal stability, Preliminary development of perovskite-based OSMs would be a reasonable research strategy. Further research efforts should be by incorporating PGM metals into novel perovskite structures with outstanding OSCs This will require the development of advanced TWCs. Improved catalytic activity and oxidation by stabilizing the metal against sintering, reaction with the support, and volatilization. and improved stability were previously reported 16-20 .

[0006] Oxygen mobility in perovskites increases with the amount of available oxygen vacancies. Doping of the A and B sites with cations occurs due to structural defects (anion or cation vacancies). ) to affect oxygen mobility. 21 Previous XRD analysis showed that By varying the type, position and degree of doping of the dopants, La-Mn perovskite was Doping with Ca, Sr and Al can be used to modify the bismuth oxide structure. It was confirmed that 6 The A site is a lower valence cation, such as an alkali metal ion. When partially substituted, the oxidation state of the cation at the B site increases to maintain electroneutrality. or some oxygen vacancies are created 22 For example, La 3+ Partly Sr 2+ By increasing the amount of unstable B ions and oxygen vacancies, Charge compensation is achieved, thereby enhancing oxygen diffusion from the bulk to the surface 23 . B The cationic nature of the site modifies the morphology, structural symmetry, charge compensation mechanism, and redox properties. R 3 In the air-H2 cycle redox reaction, La is present at the A site and Co or found that Mn-containing perovskite was the most active. 9,24 Ion valence ( Co 3+ / Co 2+ or Mn 4+ / Mn 2+ ) to modify concentration and oxygen mobility , Sr 2+ and Ce 4+ By partially replacing the A cation with Efforts have also been made to further increase 1 Klimkowicz et al. 0.5 S r 0.5 Co 0.5 Fe 0.5 O 3-δ Perovskite is the cutting edge of Ce x O y -ZrO2 It was reported that the (CZO) system exhibited a higher reversible OSC than the (CZO) system. 2 Ran et al. LaMnO 3-δ Perovskite exhibits very large dynamic OSC and high oxygen release rate, Mn 4+ / Mn 3+ The results show that redox couples contribute to redox reactions at low temperatures. Ta 13 These La-containing compositions have high redox energy storage capacity, but lower For applications at high temperatures (<1000°C), e.g. TWC mode, it is not cost-effective. In the TWC mode, more cost-effective compositions with Earth-abundant cations are Preferred.

[0007] In addition, doping the B site with PGM metals (Pd, Rh, or Pt) also results in catalytic It will increase activity and provide a "self-regenerating" effect. 25 PGM-containing perovskite solid solution In the body, PGMs are reduced to their metallic state and, after reduction, are dispersed as small particles on the surface, Tanaka et al. were the first to report that the solid solution was restored after reoxidation, and other researchers This is supported by the finding that PGM-containing perovskites can be used to reduce the amount of CO2 emitted by fuel-rich automobile exhaust pipes. It suggests that the catalysis can regenerate itself under certain conditions, and is therefore an "intelligent catalyst." The new product was named "Illuminent Catalyst" 17,18,20,26 .since then , HC, CO, and NO under transient air-fuel ratio oscillation conditions and at various temperatures. x Conversion Then, Pd-doped La 0.7 Sr 0.3 CoO3, LaAlO3 and LaFeO 3 and PGM-doped perovskites such as Rh-doped CaTiO3. Excellent catalytic activity and stability were found 27-29 .

[0008] U.S. Patent No. 4,321,250 (Hart, Phillips Petroleum ) is a compound in which rhodium ions occupy about 1% to a maximum of about 20% of the B cation sites, and the remaining The B site of the perovskite-type catalyst is occupied by cobalt (Co), and the rhodium ( Rh) is disclosed. 0.8 Sr 0.2 Co 0.95 Rh 0.05 Catalyst with O3 A, and Catalyst A in combination with an alumina support are disclosed.

[0009] U.S. Patent No. 6,680,036 (Fisher et al., Johnson Matthey ) disclose a three-way catalyst containing an oxygen storage component using the mixed oxide MnZr. Comparative data with palladium supported catalysts and CeZr catalysts is presented.

[0010] U.S. Patent Application Publication No. 2004 / 0024071 (Meier) discloses a method for the preparation of Group VIII metals. Perovskite containing iron, cobalt, ruthenium, and nickel, and synthetic gas and carbon The authors disclose their use as catalysts for the conversion of LaF e 0.5 Ti 0.5 O3, LaFe 0.5 V 0.5 O3, LaFe 0.5 Cr 0.5 O3 , LaFe 0.5 Mn 0.5 O3 and LaFe 0.5 Zr 0.5 O3 is disclosed .

[0011] U.S. Patent No. 7,718,562 (Gandhi et al., Ford Global Tech The new fusion technologies have a perovskite-based first catalyst and a second catalyst containing a precious metal. Specifically, the two-component catalyst is 0.5 Ba 0.5 Co 0.9 Pt0 .1 O3, La 0.5 Ba 0.5 Co 0.9 Rh 0.1 O3, La 0.5 Ba 0.5 Fe 0.3 Pt 0.1 O3 is disclosed.

[0012] 3. Disclosure Overview Summary of the Invention

[0013] The present disclosure provides, in embodiment 1, a platinum group metal and a zeolite of formula CaCo 1-x Zr x O 3-δ (before In the formula, x is a number defined by 0.02≦x≦0.98, and δ is a number defined by 0.0≦δ and a perovskite having a .alpha.-.alpha.-.beta. can be.

[0014] In embodiment 2, the platinum group metal is Pd, Pt, Rh, Ru, or a combination thereof. 2. The catalyst of embodiment 1, wherein the catalyst is a combination of

[0015] In embodiment 3, the platinum group metal is a combination of Pd and Rh. Catalyst according to claim 2.

[0016] In embodiment 4, the Al2O3 support, the titania support, the zirconia support, the ceria support, on a silica support, an alumina-silica support, a zeolite support, or a carbon support; The catalyst according to any one of embodiments 1 to 3.

[0017] In embodiment 5, the monolith honeycomb block is formed. 3. The catalyst according to claim 1 .

[0018] In embodiment 6, the ceramic monolith honeycomb block is coated thereon. The catalyst according to any one of embodiments 1 to 4.

[0019] In embodiment 7, the ceramic monolith honeycomb block is cordierite. 7. The catalyst of embodiment 6, wherein the catalyst is a compound of

[0020] In embodiment 8, the catalyst according to any one of embodiments 1 to 7, which is a three-way catalyst.

[0021] In embodiment 9, NO from an internal combustion engine x reduction of carbon monoxide from internal combustion engines The method according to any one of the first to eighth embodiments, wherein the method is used to catalyze the oxidation of nitrogen and hydrocarbons. Catalyst.

[0022] In embodiment 10, the catalyst according to embodiment 9, wherein the internal combustion engine is an automobile engine. Medium.

[0023] In an eleventh embodiment, the internal combustion engine is operated under stoichiometric or lean air-fuel conditions. 10. The catalyst of embodiment 9, wherein

[0024] In embodiment 12, the internal combustion engine is configured to use a diesel fuel, an ethanol / gasoline hybrid. The catalyst of embodiment 9, fueled by hybrid fuel, gasoline or natural gas.

[0025] In embodiment 13, the ethanol / gasoline hybrid fuel is 85% ethanol. 13. The catalyst of embodiment 12, wherein the fuel is ethanol / 15% gasoline (E85).

[0026] In embodiment 14, a method for reducing emissions from an internal combustion engine, comprising: contacting an exhaust stream from a combustion engine with a catalyst, said catalyst comprising a platinum group metal and a metal of the formula Ca Co 1-x Zr x O 3-δ (wherein x is defined by 0.02≦x≦0.98) where δ is a number defined by 0.0≦δ≦1.0. A method is provided comprising:

[0027] In embodiment 15, the platinum group metal is Pd, Pt, Rh, Ru, or a mixture thereof. 15. The method of embodiment 14, wherein the

[0028] In embodiment 16, the catalyst is on an Al2O3 support. 5. The method according to claim 5.

[0029] In embodiment 17, the internal combustion engine is operated under stoichiometric air-fuel ratio conditions. 17. The method according to any one of 4 to 16.

[0030] In embodiment 18, the internal combustion engine is configured to use a diesel fuel, an ethanol / gasoline hybrid. 18. Any one of embodiments 14 to 17, wherein the fuel is hybrid fuel, gasoline or natural gas. The method described.

[0031] In embodiment 19, an exhaust system for reducing emissions from an internal combustion engine is provided, comprising: , a platinum group metal and a compound of formula CaCo 1-x Zr x O 3-δ (In the above formula, x is 0.02≦x≦0 .98, and δ is a number defined by 0.0≦δ≦1.0. and a solid support. is provided.

[0032] In embodiment 20, the formula CaCo 1-x Zr x O 3-δ (In the above formula, x is 0.02 ≦x≦0.98, and δ is defined by 0.0≦δ≦1.0. A perovskite catalyst having a

[0033] In embodiment 21, the x is a number defined by 0.2≦x≦0.8. 21. The catalyst of embodiment 20.

[0034] In embodiment 22, the compound is in the form of particles having a diameter of more than about 1.0 nm and less than about 10 mm. The catalyst according to any one of embodiments 19 to 21.

[0035] In embodiment 23, the particles have a diameter greater than about 1.0 μm and less than about 50 μm. 23. The catalyst of embodiment 22.

[0036] In embodiment 24, the formula CaCo 1-x Zr xO 3-δ (In the above formula, x is 0.02 ≦x≦0.98, and δ is defined by 0.0≦δ≦1.0. A method for producing a perovskite catalyst having a (a) Dissolution of Ca, Co and Zr salts to form a homogeneous solution; (b) drying the solution; and (c) forming a perovskite catalyst by calcination and sintering. It will be offered.

[0037] In embodiment 25, the firing is performed at about 300° C. to about 500° C., and the sintering 25. The method of embodiment 24, wherein the heating is performed at about 800° C. to about 1400° C.

[0038] In embodiment 26, there is provided a method for producing hydrogen by thermochemical water splitting, comprising the steps of: (a) To release oxygen and produce an oxygen-deficient perovskite catalyst of the formula CaCo1 -x Zr x O 3-δ (In the above formula, x is a number defined by 0.02≦x≦0.98.) where δ is a number defined by 0.0≦δ≦1.0. heating the medium; and (b) releasing hydrogen to regenerate the oxygen-deficient perovskite catalyst; A method is provided that includes contacting particles of a kite catalyst with water.

[0039] In embodiment 27, the hydrogen is produced in a fluidized bed reactor. How to.

[0040] In embodiment 28, the fluidized bed reactor is a circulating fluidized bed reactor, a bubbling fluidized bed reactor. 28. The method of embodiment 27, wherein the reactor is a transport reactor or a chemical loop reactor.

[0041] In embodiment 29, the hydrogen is produced in a fixed bed reactor. How to.

[0042] In embodiment 30, the perovskite catalyst is heated at a temperature of about 400° C. to about 1000° C. 30. The method of any one of embodiments 26 to 29, wherein the heating is performed at 40.degree.

[0043] In embodiment 31, the following reaction is carried out to reduce carbon dioxide to carbon monoxide and water: Any of embodiments 26 to 30, further comprising using hydrogen produced in the reactor. How to.

[0044] In embodiment 32, carbon dioxide or carbon monoxide is reduced to hydrocarbons and water. 31. The method of any one of embodiments 26 to 30, further comprising using hydrogen produced in a subsequent reactor to Any method as described above.

[0045] In embodiment 33, carbon dioxide or carbon monoxide is reacted with an alkane or alkene.

[0023] The embodiment further comprising using hydrogen produced in the next reactor to reduce hydrogen to water. A method according to any one of 26 to 30.

[0046] In embodiment 34, a method for producing an aldehyde from a mixture of carbon monoxide and an alkene is provided.

[0036] Embodiments 26 to 30 further comprising using hydrogen produced in a subsequent reactor to 2. The method according to claim 1 ,

[0047] In embodiment 35, the quality of the crude oil, heavy petroleum or biomass oil feedstock is To improve the quality, the hydrogen produced in the next reactor is subjected to hydrotreating or hydroprocessing. 31. The method of any one of embodiments 26 to 30, further comprising using the same for stimulating the immune system.

[0048] In embodiment 36, the carbon dioxide is generated in a chemical looping combustion fuel reactor. generated in the AL looping combustion fuel reactor 32. The method of embodiment 31, wherein

[0049] In embodiment 37, there is provided a method for reducing carbon dioxide to carbon monoxide, comprising the steps of: (a) To release oxygen and produce an oxygen-deficient perovskite catalyst, a compound of the formula CaCo 1- x Zr x O 3-δ (In the above formula, x is a number defined by 0.02≦x≦0.98.) where δ is a number defined by 0.0≦δ≦1.0. heating the medium; and (b) removing oxygen, releasing carbon monoxide, and regenerating the perovskite catalyst; contacting the oxygen-deficient perovskite catalyst with carbon dioxide to Provided.

[0050] In embodiment 38, a system for thermocatalytic decomposition of water to produce hydrogen is provided. It is (a) forming an oxygen-deficient perovskite catalyst and releasing oxygen by reacting a compound of the formula CaCo 1-x Zr x O 3-δ (In the above formula, x is a number defined by 0.02≦x≦0.98.) where δ is a number defined by 0.0≦δ≦1.0. an oxygen generating reactor for heating the catalyst; (b) reacting the oxygen-deficient perovskite catalyst with water vapor and forming a hydrogen peroxide-containing perovskite catalyst; a hydrogen generation reactor for regenerating the catalyst and producing hydrogen; and (c) configured to return the regenerated perovskite catalyst to the oxygen generation reactor. A system is provided that includes an apparatus.

[0051] In embodiment 39, the oxygen generating reactor is a fluidized bed reactor. The system is as follows:

[0052] In embodiment 40, the hydrogen generation reactor is a fluidized bed reactor. 39. The system according to claim 39.

[0053] In embodiment 41, the hydrogen generating fluidized reactor is a riser reactor. The system described in

[0054] In embodiment 42, either the oxygen generation reactor or the hydrogen generation reactor comprises: 39. The process of embodiment 38, which is a fixed bed reactor.

[0055] In embodiment 43, the hydrogen is used to reduce carbon dioxide in exhaust gases from a combustion process. The system according to any one of embodiments 38 to 42, which is used for recovering a signal.

[0056] In embodiment 44, the hydrogen is used for thermal energy storage. 38 to 43. A system according to any one of claims 38 to 43.

[0057] In embodiment 45, the energy for the water splitting reaction is increased while minimizing the energy loss. In one embodiment, the present invention is integrated into a chemical manufacturing system and a chemical manufacturing facility that provides energy. 38 to 44. A system according to any one of claims 38 to 44.

[0058] In embodiment 46, a platinum group metal and a palladium compound of the formula (La1-y Ca y ) 1-x Mn x O 3-δ , La 1-x (Co 1-y Ru y ) x O 3-δ , (La 1-y Sr y ) 1-x Co x O3 -δ , Sr 1-x (Co 1-y Fe y ) x O 3-δ , (Sr 1-y Ca y ) 1-x Fe x O 3-δ (In the above formula, x is a number defined by 0.02≦x≦0.98, and y is , 0.02≦y≦0.98, and δ is a number defined by 0.0≦δ≦1.0. and a perovskite having a ZnO content of 0.1 to 0.25, where ZnO is a number defined as 0.1 to 0.25.

[0059] In embodiment 47, the y is a number defined by 0.15≦y≦0.85. 47. The catalyst of embodiment 46,

[0060] In embodiment 48, the x is a number defined by 0.3≦x≦0.7. 48. The catalyst of embodiment 46 or 47.

[0061] In embodiment 49, the platinum group metal is Pd, Pt, Rh, Ru, or any of their equivalents. 49. The catalyst of any one of embodiments 46 to 48, which is a mixture.

[0062] In embodiment 50, the platinum group metal is a mixture of Pd and Rh. 10. The catalyst according to claim 9.

[0063] In embodiment 51, the Al2O3 support, the titania support, the zirconia support, the ceria support , on a silica support, an alumina-silica support, a zeolite support, or a carbon support. 51. The catalyst according to any one of embodiments 46 to 50.

[0064] In embodiment 52, the honeycomb block is formed in the form of a monolith. 52. The catalyst according to any one of claims 1 to 51.

[0065] In embodiment 53, a ceramic monolith honeycomb block is coated thereon. 53. The catalyst according to any one of embodiments 46 to 52.

[0066] In embodiment 54, the ceramic monolith honeycomb block is made of cordierite. The catalyst of embodiment 53, which is a compound.

[0067] In embodiment 55, the catalyst according to any one of embodiments 46 to 54, which is a three-way catalyst. .

[0068] In embodiment 56, NO from an internal combustion engine x or carbon monoxide from internal combustion engines 55. Any of embodiments 46 to 54, wherein the compound is used to catalyze the oxidation of nitrogen or hydrocarbons. The catalyst according to claim 1.

[0069] In embodiment 57, the internal combustion engine is an automobile engine. catalyst.

[0070] In embodiment 58, a method for reducing emissions from an internal combustion engine, comprising: contacting an exhaust stream from a combustion engine with a catalyst, the catalyst comprising a platinum group metal and a metal of the formula (L a 1-y Ca y )1-x Mn x O 3-δ , La 1-x (Co 1-y Ru y ) x O 3-δ , (La 1-y Sr y ) 1-x Co x O 3-δ , Sr 1-x (Co 1-y Fe y ) x O 3- δ , (Sr 1-y Ca y ) 1-x Fe x O 3-δ (In the above formula, x is 0.02≦x≦0. 98, and y is a number defined by 0.02≦y≦0.98. where δ is a number defined by 0.0≦δ≦1.0. and

[0071] In embodiment 3, an exhaust system for reducing emissions from an internal combustion engine, comprising: Platinum group metals and the formula (La 1-y Ca y ) 1-x Mn x O 3-δ , La 1-x (Co 1-y Ru y ) x O 3-δ , (La 1-y Sr y ) 1-x Co x O 3-δ , Sr 1-x (Co1 -y Fe y ) x O 3-δ , (Sr 1-y Ca y )1-x Fe x O 3-δ (In the above formula, x is , 0.02≦x≦0.98, and y is a number defined by 0.02≦y≦0.98 where δ is a number defined by 0.0≦δ≦1.0) and a solid support. will be done. [Brief description of the drawings]

[0072] [Figure 1] X-ray diffraction (XRD) patterns of state-of-the-art perovskite samples with different A-site ions and B-site ions (Fig. 1A). X-ray diffraction (XRD) patterns of RTI's novel CaCoxZr1-xO3-δ perovskite samples with and without Pd doping (Fig. 1B). [Diagram 2] Oxygen nonstoichiometry (δ) as a function of sample temperature for as-synthesized perovskite samples compared to commercial CZO and CeO2. Results are calculated using temperature programmed thermogravimetry (TG) data, assuming an onset temperature of thermal oxygen evolution of 500 °C (after complete sample outgassing). [Diagram 3] The amount of CO2 production and CO uptake, represented by the MS signal (in partial pressure) versus time on stream (TOS), and the temperature of the test sample, were recorded during the CO-TPR / MS measurements (Figure 3A, Figure 3B). [Figure 4] H2 consumption as a function of on-stream reaction time and temperature of the test sample during H2-TPR measurements (temperature ramp rate 5 °C / min). [Diagram 5] CO2 production and O2 uptake versus time on-stream reaction (TOS) for PE-1–PE-6 perovskites compared to CeO2 and CZO, as represented by MS partial pressure signals during isothermal CO reduction-air oxidation cycling tests at 500°C, 600°C, 700°C, and 800°C (Figures 5A–B). [Figure 6]CO2 production and O2 uptake versus time on-stream reaction (TOS) for PE-6–PE-9 perovskite samples (CaCoxZr1-xO3-δ, x = 0.3, 0.5, 0.7, or 0.9) as represented by MS partial pressure signals during isothermal CO reduction-air oxidation cycle tests at 500°C, 600°C, 700°C, and 800°C. [Figure 7] Plots for the kinetic calculation of oxygen uptake in CaCo0.5Zr0.5O3-δ perovskite samples, including plots of reaction fraction α versus time (FIG. 7A), plots of reaction fraction α versus reduced time t / t0.5 (FIG. 7B), and ln[-ln(1-α)] as a function of lnt (t in minutes) (FIG. 7C) for the determination of the reaction mechanism at temperatures ranging from 350°C to 475°C. [Figure 8] Temperature-dependent reaction rate constant k on the natural logarithmic scale as a function of inverse temperature for the calculation of the reaction activation energy of CaCo0.5Zr0.5O3-δ perovskite. The k values ​​were obtained by fitting the reaction data to various kinetic models, with the first-order kinetic model being chosen. [Figure 9] (1) CO conversion and (2) C3H8 conversion during catalytic oxidation tests for CaCo0.5Zr0.4Pd0.1O3-δ perovskite (panels 1a / 2a), CaCo0.55Zr0.4Pd0.05O3-δ perovskite (panels 1b / 2b), and CaCo0.5Zr0.5O3-δ perovskite (panels 1c / 2c) with simulated exhaust feeds of stoichiometric number (SN) 1.16, 1.07, and 0.95. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0073] 5. Detailed Description of the Disclosure 5.1.Definition Although the following terms are believed to be well understood by those of ordinary skill in the art, the following definitions are used herein. It is provided to facilitate explanation of the subject matter disclosed in the document.

[0074] As used herein, the term "oxygen storage material" (OSM) refers to a material that can reversibly store gas phase oxygen. It means a stable material that has both the ability to absorb and release said oxygen. In one embodiment, such as a gas, the OSM is NO x absorbs oxygen from the Alternatively, oxygen can be released to oxidize carbon monoxide. The perovskite catalyst is OSM. This perovskite catalyst is x O y -ZrO2(C It can be combined with conventional OSMs such as mixed oxides (ZO).

[0075] The term "perovskite" refers to perovskite having a cubic crystal morphology and the formula ABO 3-δ Or A l A 2 B 1 B 2 O 3-δ The cations A and B are metal oxides having multiple valences. It is a metal that can take any state and is stable in both octahedral and dodecahedral environments.

[0076] The term "platinum group metals" or (PGM) refers to Group VIII metals from the periodic table. Preferred PGMs are Pd, Pt, Rh, Ru, or combinations thereof.

[0077] The term "three-way catalyst" or (TWC) refers to a catalytic converter that is used for the oxidation of CO, the oxidation of unburned hydrocarbons (HC), or Or NO x to N2, usually at a faster rate or at a lower temperature. The three chemical reactions occur simultaneously or This occurs with staged catalyst systems such as the TWC system disclosed in US Pat. No. 7,718,562. In U.S. Pat. No. 7,718,562, the first catalyst is NO x Reduce the second The catalyst oxidizes CO and HC. In a staged catalytic system, the peroxidase disclosed herein Buskites are available as either first stage catalysts, second stage catalysts, or both stage catalysts. It may be present as a component.

[0078] Throughout this specification, the terms "about" and / or "approximately" refer to numerical values ​​and / or The term "about" may be used in conjunction with numerical ranges. It is understood that the term "about" means a value close to the recited value. For example, "about 40 [units]" means within ±25% of 40 (e.g., 30 to 50), ± Within 20%, Within ±15%, Within ±10%, Within ±9%, Within ±8%, Within ±7%, Within ±6 Within ±5%, Within ±4%, Within ±3%, Within ±2%, Within ±1%, Less than ±1% It may mean within, or any other value or range of values ​​therein or therebetween. Additionally, the phrases "less than about [value]" or "greater than about [value]" are used herein to refer to any The terms "about" and "approximately" should be understood in light of the definition of the term "about" provided in the document. The terms "other" and "others" may be used interchangeably.

[0079] Throughout this specification, numerical ranges are given for specific amounts. These ranges are It is to be understood that the range includes all subranges within the range. Thus, "from 50 to 80" The range includes all possible ranges within it (e.g., 51-79, 52-78, 53-77). , 54-76, 55-75, 60-70, etc. In addition, all values ​​within a given range The value may be an end point of a range encompassed by the given range (e.g., 50 to 80). Ranges include ranges having endpoints such as 55 to 80, 50 to 75, etc.

[0080] As used herein, the verb "comprise" as used in the specification and claims is used interchangeably. "omprise" and its variants are used in a non-restrictive sense and are followed by the word It is meant that the items that follow are included, but that items not specifically mentioned are not excluded.

[0081] Throughout this specification, the terms "comprising" or "including" are used interchangeably. Variations such as "comprising" or "comprising" are used to refer to the contains a set of elements, integers or steps, or a group of elements, integers or steps but any other element, integer or step or It will be understood that no exclusion of the group of groups is meant. The claims properly "comprise" steps, elements, and / or reagents. "consist of" the steps, elements, and / or reagents described, as appropriate. " or "essentially free" from the claimed steps, elements, and / or reagents, as appropriate. It can "consist essentially of."

[0082] It is further understood that the claims may be drafted to exclude any optional element. Thus, this statement should not be construed as a recitation of claim elements or a "negative" limitation. In relation to the use, exclusive terms such as "solely" and "only" It is intended to serve as an antecedent for the use of

[0083] Unless otherwise defined, all technical and scientific terms used herein are , have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure pertains. Any methods and materials similar or equivalent to those described herein may be used in the practice of the present disclosure. Although preferred methods, apparatus, and materials may be used in the practice or testing, All references cited herein are incorporated by reference in their entirety. do.

[0084] The following examples further illustrate the present disclosure, but are not intended to limit the scope. In particular, the present disclosure is not limited to the particular embodiments described, which in themselves are not intended to be limiting. It is understood that variations may occur, of course. The scope of the present disclosure is defined by the appended claims. Therefore, the terminology used herein is intended to describe particular embodiments only. It should also be understood that the present invention is intended to be illustrative and not limiting. . EXAMPLES

[0085] This study explores the potential of commercially available CZO in three-way catalyst (TWC) structures for automotive applications. The focus of this research is on the systematic screening of advanced perovskites as potential alternatives to ferroelectrics. Some of the perovskite compositions used in the synthesis have demonstrated significant material performance in other applications. The study was selected based on the most recent literature reporting 30-34 CaCo x Zr 1-x O3 -δ Perovskites were first synthesized and today's state-of-the-art perovskite materials and commercially available It is herein shown that, compared to CZO, it exhibits superior redox properties and oxygen mobility. Reported here is the CO storage of the as-synthesized material compared to commercial CZO and CeO2. To investigate the oxygen storage capacity and CO temperature programmed oxidation measurements, H2 temperature programmed oxidation measurements were performed. The temperature-dependent oxygen To investigate the correlation between the number of vacancies and the redox properties of the materials, oxygen nonstoichiometry measurements were applied. The test materials were characterized using X-ray fluorescence, X-ray diffraction, and BET surface area measurements. The results include kinetic data on oxygen uptake for the best performing perovskite materials. This study provides a comprehensive comparison of the oxygen storage / oxygen release capacities of current state-of-the-art perovskite materials. for comparison and development of high performance perovskite materials in automotive and other potential applications. The aim of this study is to provide preliminary results for

[0086] 2. Experimental Method

[0087] 2.1. Synthesis of perovskite materials

[0088] Using the Pechini method, CaCo x Zr 1-x O 3-δ (x=0, 0 0.3, 0.5, 0.7 and 0.9) and Pd-doped CaCo 0.6-y Zr 0.4 P d y O 3-δ Perovskites with target compositions of (y=0.05, 0.1, and 0.2) The compound was 35 Calcium nitrate tetrahydrate (Sigma-Aldrich, St. Louis, MO) Cobalt(II) nitrate hexahydrate (STREM Chemical, New York, NY) (Buryport, Massachusetts), zirconium(IV) oxynitrate hydrate (Si gma-Aldrich) and palladium(II) nitrate dihydrate (Alfa Aesa r, Tewksbury, Massachusetts) was used as the metal precursor. Amounts of metal nitrates were first added to ethylene glycol (Acros Organics, Pittsburgh, (Pennsylvania, USA) and then mixed in a molar ratio of n (metal):n (citric acid): n (ethylene glycol) = 2:3:9, citric acid (Fisher Chemical A solution was formed at 150° C., and then the mixture was stirred at 30° C. for 1 hour. The mixture was slowly heated to 250°C with continuous stirring until a solid gel was formed, then heated to room temperature. Calcination was then carried out at 400 °C for 4 h, followed by a constant flow of dry air (5 mL / min ) was used and sintered in a high-temperature oven at 1200 °C for 4 hours. x O y -Zr O2 (CZO, Ce:Zr=1:4 (molar ratio)) and CeO2 are MEL C hemical (Flemington, NJ) and Alfa Aesar Got it. La 0.6 Sr 0.4 Chief of Staff 3-δ , Sr 0.76 Ca 0.24 FeO 3-δ , LaCo 0.6 Ru 0.4 O 3-δ , SrCo 0.85 Fe 0.15 O 3-δ , and La 0.5 Ca 0.5 MnO 3-δ Other perovskites, including 30-34 .

[0089] 2.2. Oxygen non-stoichiometry test

[0090] The temperature-dependent oxygen nonstoichiometry (δ) of the as-synthesized perovskite samples was measured using TA Q5 The test was performed by temperature programmed thermogravimetric analysis (TGA) using 0.00 units. First, 0 mg of the sample was placed on a platinum dish and heated at 500 °C for 2 h in helium at a flow rate of 60 mL / min. The weight loss of the degassed sample was then measured in helium at the same flow rate from 500°C to The temperature was increased from 0.2 to 900°C at a ramp rate of 5°C / min. Assuming that 00°C is the onset temperature of thermal oxygen evolution, this was correlated with the weight loss of the samples. Sales Ce x O y -ZrO2(CZO, Ce:Zr=1:4 (molar ratio), MEL Chem The hypothetical oxygen nonstoichiometry of CeO2 (Alfa Aesar) and CeO2 (CeO2) is also The calculations were carried out in comparison with the perovskite tested. Background measurements using a platinum dish were performed using the same reaction program.

[0091] 2.3.CO-Temperature Programmed Reduction Measurement

[0092] The CO-temperature programmed reduction ( The CO-TPR measurements were performed using a Micromeritics Au A toChem II 2920 reactor was used, and a benchtop quadrupole mass spectrometer was used downstream of the reactor. Connect to the analyzer (TA Discovery Mass Spectrometer) The TCD signal was used to quantify the CO uptake, while the MS signal was used to quantify the CO uptake. It was used for identification and semi-quantifiable analysis of synthetic gases. Approximately 0. A 5 g sample was first placed in a U-shaped quartz reactor housed in a thermal furnace with an upper temperature limit of 1000°C. After degassing for 1 hour at 500 °C in He with a flow rate of 50 mL / min, the TCD and MS responses were The samples were circulated in 20% CO / He at a flow rate of 30 ml / min, with recordings every 0.1 s. The temperature was increased from ambient temperature (25°C) to 900°C at a rate of 5°C / min. The TCD calibration for CO and increased CO2 yielded linear calibration curves for both CO and CO2. The baseline gas was 20% CO / He. To create a background run, a blank reactor and the same reaction conditions were used. I did.

[0093] 2.4.H2-Temperature Programmed Reduction Measurement

[0094] H2-temperature programmed reduction ( H2-TPR) measurements were carried out using the same AutoChem reactor system as above. First, about 0.5 g of the sample was degassed for 1 hour at 500 °C in He with a flow rate of 50 mL / min. The sample was heated from ambient temperature (25°C) to 90°C in 10% H2 / Ar at a flow rate of 30 ml / min. The temperature was increased to 0°C at a rate of 5°C / min. The water generated during TPR was cooled with a mixture of propanol and liquid N2. The TCD calibration was performed in Ar. The H2 concentration was changed from 0% to 10% and 10% H2 / Ar was used as the reference gas. To create a baseline, an empty reactor and a batch reactor with the same reaction conditions were used. Background testing was conducted.

[0095] 2.5. Dynamic Measurement of CO Storage Capacity and Oxygen Storage Capacity

[0096] The oxygen mobility in the test sample was measured using the same AutoChem reactor system as above. This was further investigated using a quantitative isothermal CO-air redox cycle test. First, the sample was degassed in He (50 mL / min) at 500 °C for 2 h. Each cycle consisted of Following the CO reduction-air oxidation sequence, the temperatures were 500°C, 600°C, 700°C, and 800°C. Each reaction was carried out in three cycles at each reaction temperature. During reduction, 20% CO / H e was flowed through the sample at a constant flow rate of 30 mL / min. During oxidation, air (without moisture) was flowed for 30 The sample was passed through the solution at a constant flow rate of mL / min. The reduction and oxidation periods were both 0.5 min (3 Between the reduction and oxidation steps, the remaining system was diluted with He at a flow rate of 50 mL / min. The distillate gas was purged. CO2 production during the reduction cycle and O2 uptake during the oxidation cycle The reaction was closely monitored by TCD and MS signals. A background test using was performed under the same cycle conditions.

[0097] 2.6. Isothermal Thermogravimetric Experiments for Reaction Kinetics Testing

[0098] The best performing perovskite kinetics was performed using a TA Q500 unit. The tests were carried out by isothermal thermogravimetry (TG) experiments. Approximately 20 mg of each test sample was added to 50 mL of He / min) at 500 °C for 1 h, then in 20% CO / He (30 mL / min) The sample was pre-reduced at the same temperature for 1 hour. Then, the above pre-treated sample was placed in a shallow platinum dish and At a rate of 60 mL / min, the target temperatures (350°C, 375°C, 400°C, 425°C, The samples were heated to 50°C, 475°C, or 500°C. The weight signal of the samples was measured throughout the entire process. The target temperature was reached and a stable baseline was obtained while recording the temperature every 0.1 seconds. Afterwards, the flow was switched to 5% O2 / He to gradually oxidize the sample. To confirm the kinetics of the reaction, background measurements using an empty platinum dish were performed at each reaction temperature. The model is adapted from previous work by Hancock

[29] and Motohashi

[30] . The main calculation formulas are provided in the accompanying text.

[0099] 2.7. Catalyst characterization

[0100] 2.7.1. X-ray Fluorescence (XRF) Analysis

[0101] X-ray fluorescence analysis (XRF) for elemental composition testing of test materials was performed by Thermo Science. The ARL PERFORMX wavelength dispersive X-ray fluorescence (WDXRF) instrument manufactured by ntific was used. The experiment was carried out using a 5GN type Rh target with an extremely thin 30 μm Be window. The instrument uses two detectors to achieve a wide elemental range. The sample data was collected using a 1000-millimeter GC / MS detector and seven analyzer crystals to determine elemental concentrations. Unix is ​​a standard software package that uses advanced basic parameter algorithms. The data was processed using Quant. 79 elements were analyzed and the instrument calculated Elements with uncertainties exceeding 10 times are reported.

[0102] 2.7.2. X-ray Diffraction (XRD) Analysis

[0103] Phase identification was performed using a Thermo INEL Equinox 100 benchtop X-ray This was done by X-ray diffraction (XRD) analysis of the test materials using a diffractometer. XRD patterns The data were collected monochromatically at instrument output settings of 40 kV and 0.9 mA, with a total scan duration of 1200 seconds. Using CuKα radiation, 2θ is 20 to 70 o The data was collected from a range of vendors. Using Y2O3 standard product peak accuracy, the instrument was verified by comparison with ICDD PDF standards. A scan was performed for verification. The accuracy of the Y2O3 standard product peak is 2θ All measurements were performed using Jade software. and was processed.

[0104] 2.7.3.BET surface area analysis

[0105] The BET surface area of ​​the test materials was measured using ASAP 2020 Plus Chemistry Each sample (approximately 0.2 g) was first measured using a vacuum (<500 μm The degassed sample was degassed at 350°C for 4 hours in a 100% Hg bath. The multi-point BET surface area of ​​the degassed sample was measured at 350°C in a 100% Hg bath at liquid nitrogen temperature. The measurements were performed at 37°C (77K) and partial pressures (P / P0) of 0.05 to 0.30.

[0106] 3. Results and Discussion

[0107] 3.1. Structural analysis of test samples

[0108] The actual composition of the as-synthesized perovskite samples was replicated within an error limit of <10%. The target (theoretical) and actual compositions of the test materials are shown in Table 1. The difference between the two values ​​for all perovskites is within the acceptable range. e x O y -ZrO2(CZO) and CeO2 analysis information is provided by their manufacturers. Table 1 also shows the calculated perovskite allowable temperatures based on the theoretical material composition. The capacity factors (t) are listed. The t values ​​are Ca for the A-site ions. 2+ , La 3+, and Sr 2+ Based on the ionic radius of 3+ , Fe 3+ , Mn 3 + , Ru 3+ , Zr 4+ , and Pd 2+ Calculated based on the ionic radius of PE-1 The t value of the PE-9 sample is in the range of 0.8 to 0.92, indicating that the stable orthorhombic perobic phase is Suggests kite structure 3 .

[0109] [Table 1]

[0110] Notes: a Materials measured by XRF with reproducible results and tolerance limits of less than 10% The actual composition of the ingredients; b Theoretical tolerance factor (0. in the range of 75 to 1); c At liquid N2 temperature (77K) and relative pressure (P / P0) in the range of 0.05 to 0.30 Measured multipoint specific BET surface area d Commercially available materials obtained from MEL Chemical and with information on material composition provided. CZO sample. ; e A commercially available C1000 series was obtained from Alfa Aesar and provides information on the material composition. eO2 sample.

[0111] More detailed material structure information of the test material can be obtained from XRD analysis. B plots the highly resolved XRD patterns of all fresh samples. FIG. 1A shows the as-synthesized peroxidase with different A-site and B-site ions. The XRD patterns of the La bismuth oxide samples PE-1 to PE-5 are shown. 0.6 Sr 0.4 Co O 3-δ The XRD pattern of (PE-1) was obtained from the database (PDF#01-070-75 97) and is consistent with previous reports. 30 , which is characteristic of a rhombohedral crystal lattice structure. 0. 76 Ca 0.24 FeO 3-δ All the diffraction peaks of (PE-2) are due to perovskite-type Can be attributed to structure (PDF#01-082-2445) 31 LaCo 0.6 Ru 0.4 O 3-δ The diffraction pattern of the sample (PE-3) shows peaks due to ruthenium oxide. A program for a single perovskite structure (PDF#01-082-9769) without any defects Show file 32 .SrCo 0.85 Fe 0.15 O 3-δ XRD of sample (PE-4) The pattern also showed no impurity phases and was consistent with the previously reported perovskite structure (PDF#0 4-014-2297) 33 La 0.5 Ca 0.5 MnO 3-δ (PE -5) was previously reported as La 0.67 Ca 0.33 MnO3 Perovskite (PDF #04-014-6391), which showed a clear peak that matched well with

[0112] XRD patterns of the novel perovskite samples of PE6-12 with and without Pd doping. The line is shown in Figure 1B. The 2θ values ​​are 22.1, 31.0, 31.5, 32.0, 45.2, and 50 .2, 50.9, 51.6, 55.2, 55.9, 56.5, 56.7, 64.7, 65 The reflections at 66.9 and 67.8 are from the orthorhombic Lakargiite CaZrO3 perobic system. It is assigned to the main phase of the kite matrix (JCPDS 01-080-6213); The reflections at 30.3, 35.1, 50.5, 60.0 and 63.0 are from the cubic Tazh eranite ZrO2 structure (JCPDS 04-002-8314);2 At θ of 19.5, 32.5, 34.2, 41.6, 42.3, 46.4, and 47.8 The reflections are assigned to the Ca3Co2O6 phase (JCPDS 04-010-0812); The reflections at 40.2 and 46.7 were assigned to Pd phases (JCPDS 01-089 -4897).

[0113] CaCo with lower x value (higher Zr / Co ratio in B site) x Zr 1-x O3 exam For the materials, an increase in the amount of ZrO2 phase was detected, while the amount of the main perovskite phase was higher. Crystallinity was observed. When x>0.7, a significant amount of Ca3Co2O6 phase was detected. This suggests that the partial substitution of Co by Zr enhances the structural crystallinity of CaCoO3. When the x value is about 0.5, CaCo 0.5 Zr 0.5 O3 has optimal crystallinity and minimal It is noteworthy that when x<0.7, there is no single form of cobalt oxide. No lateral phases of Co were identified, suggesting that Co is located inside the perovskite unit cell.

[0114] CaCo 0.6-y Zr 0.4 Pdy For the O3 sample, the characteristic peak was CaCo 0.5 Zr 0.5 Since this coincides with that observed in O3, the main phase is CaCo x Zr 1-x O 3 perovskite. A peak characteristic of Pd was observed, indicating an increase in Pd loading. The amount of Pd phase increased with increasing temperature. No peak corresponding to PdO was observed. Some of the deposited Pd is incorporated into the bulk crystal structure of the perovskite (bulk Pd 2+ ) and some remain on the crystal surface (surface Pd 0 ) is also suggested. Bulk Pd 2+ The existence of is further confirmed by the results of H2-TPR in the following text. will be proved.

[0115] 3.2. Temperature-dependent oxygen nonstoichiometry of as-synthesized perovskite

[0116] Temperature of as-synthesized perovskite samples and commercial CeO2 and CZO samples The dependent oxygen nonstoichiometry (δ) is compared in the temperature range of 500°C to 900°C in Figure 2. In general, the δ value increases with increasing temperature. This is observed between the perovskite sample and the Ce-containing non-perovskite sample. Compared with the materials, CeO2 and CZO showed very little variation in δ value with temperature. Among the perovskite samples, PE-1 to PE-5 were subjected to the entire temperature program process. The δ increase rate was stable, and PE-1(La 0.6 Sr 0.4 Chief of Staff 3-δ ) is the best Compared with PE-1 to PE-5, CaCo x Zr1-x O 3-δ Perovskite type The oxygen release of skite is a more thermally activated process, with the δ value exponential at 780 °C. It was observed that the temperature increased as a function of x > 0.3 and the temperature increased from 800 to 900 °C. When the temperature reaches 100°C, a significant amount of oxygen vacancies are formed in CaCo x Zr 1-x O 3-δ This occurred in.

[0117] 3.3. As-synthesized perobs compared to commercial ceria-based oxygen storage materials (OSMs) Kite's reducibility

[0118] As-synthesized perovskite samples and commercial ceria-based oxygen storage material (OSM) samples The CO-TPR / MS profiles of the samples are shown in Figure 3. No oxidation pretreatment was performed on the fresh samples. This is because the material is exposed to an oxidizing firing environment during synthesis. The perovskite sample was heated to 1200 °C in air, and the commercial CeO2 and CZO samples were heated to about This is because the specimens have already been exposed to 550°C. Before every measurement, a thorough sample degassing pretreatment was performed. was applied. Figures 3A and 3B show the CO2-TPR product stream (Figure 3A ) Partial pressure (Torr) of mass fraction of CO2 (mass 44) and (Figure 3B) CO (mass 28) The semi-quantitative MS signal is plotted in the same manner as above. The CO2 and CO The baseline is also plotted. Positive CO2 peaks and negative CO2 peaks relative to the baseline. The CO peaks in the CO reduction test increased as the reduction temperature increased from ambient to 900°C. A higher degree of reduction of the sample indicates a higher intensity of the CO2 signal, and This is represented by a higher absolute value of CO intensity.

[0119] In Figures 3A-3B, highly resolved CO and CO signals were recorded during the CO-TPR measurements. The isolated MS signal indicates the validity of the analytical method. The onset reduction temperature of the test sample was about The reduction continues as the temperature increases to 900°C. For the , the prominent TPR peaks at different temperature ranges represent various types of solid-state reduction. For perovskite, all A cations (Ca 2+ , La 3+ and Sr 2+ )teeth Not reducible under the conditions described 3 Therefore, reduction is mainly due to B cations (Co m+ , Fe n+ , Mn p+ , and Ru q+ ) More specifically, the reduction occurred at the surface oxygen stabilized The exception was CaCo x Zr 1-x O 3-δ Perovskite Samples (PE-6 to PE-9) are Zr 4+ As mentioned above, the incorporation of On the other hand, B site Zr 4+ The ion was non-reducible under the conditions described.

[0120] In general, the volumetric amount of CO consumption (V CO , mL / g sample) is CaCo x Zr 1-x O 3- δ (x=0.9, 0.7, and 0.5) > LaCo 0.6 Ru 0.4 O 3-δ >CaC o 0.3 Zr 0.7 O 3-δ >La0.6 Sr 0.4 Chief of Staff 3-δ >La 0.5 Ca 0. 5MnO 3-δ > CeO2 > CZO > SrCo 0.85 Fe 0.15 O 3-δ >Sr 0. 76 Ca 0.24 FeO 3-δ All the as-synthesized perovskite samples The reducibility of the material is higher than that of the commercial CeO2 and CZO samples. Among them, CaCo x Zr 1-x O 3-δ exhibits good reducing properties in CO-TPR. Specifically, CaCo 0.9 Zr 0.1 O 3-δ is the current state-of-the-art La 0.6 Sr 0. 4CoO 3-δ It shows significantly higher reducing ability than

[0121] Figure 4 shows CaCo x Zr 1-x O3 and CaCo 0.6-y Zr 0.4 Pd y O3 The H2-TPR profile is shown. x Zr 1-x O3 (except CaZrO3) The TPR profile showed two consecutive reduction peaks, one of which was at 280–5 00 °C range, and the other ranges from 450 to 680 °C. Consistent with previous studies, The two peaks are 3+ From Co 2+ and Co 2+ From Co 0 to Can be attributed to reduction 36,37The amount of reducing sites increases with increasing Co content. CaZrO3 did not show any reduction, which further confirmed that reduction occurred only at the Co site. Meanwhile, the reduction temperatures of both peaks are lower with increasing Zr content. This result indicates that the substitution of B sites by Zr reduces the reduction temperature. This indicates that the reduction of Co species was promoted by the addition of ZnO.

[0122] Fresh Pd-doped CaCo 0.6-y Zr 0.4 Pd y O 3-δ H The 2-TPR profile shows a high-temperature Co reduction peak (Co 3+ From Co 2+ Lower than The Pd doping of Co 2+ from Co 0 A significant shift of the reduction peak to lower temperatures was also observed. This became more pronounced as the Pd content increased. At the maximum Pd loading, three overlapping The peaks that overlap are CaCo 0.4 Zr 0.4 Pd 0.2 O3. Higher temperatures (T ma x The two consecutive reduction peaks at 390°C and 420°C are due to Co as explained above. This can be attributed to reduction, whereas low temperature (T max = 320℃) peak is due to oxidation of Pd. Object form (Pd 2+ )Pd 0 Corresponding to the reduction 36 The peak area increases with decreasing Pd content. This is consistent with previous reports, suggesting that Pd promotes the reduction of Co to increase the catalytic activity. This suggests that the reduction ability of the surface Pd0 Hydrogen dissociation on particles and its This can be attributed to the subsequent spillover of dissociated hydrogen atoms to Co species. 38 .

[0123] Both Pd-doped and undoped perovskites are characterized by the presence of CeO2 and C The CeO2-ZrO2(CZO) sample showed higher reducibility than the eO2-ZrO2(CZO) sample. The original temperature rises from 500°C to much higher temperatures, and T max is about 800℃, and C e 4+ From Ce 3+ Attributable to reduction to 39 Addition of Zr to the CZO structure 4+ The incorporation of The reduction peak occurs at a lower temperature (T max = 520℃) In mixed ceria-zirconia, the smaller ionic radius of zirconium leads to their By eliminating the distortion associated with formation, Ce 3+ There is enough evidence to support the existence of ions. It has been established that enhanced oxygen vacancies explain the improved reducibility / OSC.

[0124] 3.4. Dynamic CO storage capacity and dynamic oxygen storage capacity of test materials

[0125] The CO storage capacity and oxygen storage capacity of the test materials were determined by measuring CO and O2 as a reducing agent and an acid, respectively. The measurements were performed using a dynamic isothermal redox cycle test in which the A volume of 20% CO / He and air were sequentially purged briefly (30 seconds) into the degassed sample. He is purged between the reduction and oxidation stages to purge out residual gases. The performance of each sample was evaluated at four redox temperatures (500, 600, 700, and The test was carried out isothermally at 200°C (800°C and 800°C), while three replicate measurements were carried out consecutively at each temperature. The gas product composition of the reaction was closely monitored by TCD and MS. Figure 6 shows the CO2 production (solid peak***) and CO2 production (solid peak***) during measurement for all test materials. MS response of unreacted O2 (dotted peak ***) (mass fraction partial pressure Specifically, Figures 5A-5B show different types of perovskite ( Comparison of material performance between OSMs (PE-1~PE-6) and commercial OSMs (CeO2 and CZO) 6 shows the results of the CaCo x Zr 1-x O 3-δ Perovska The OSC of the test materials (PE-6 to PE-9) is shown. Significant CO2 formation (CO conversion) was detected at temperatures above 500°C. In general, the redox properties were It increases with increasing temperature from 0 to 800 °C. In addition, the isothermal process It showed a relatively stable response for CO conversion and subsequent O2 storage during the oxidation stage. , suggesting stable material performance.

[0126] In Figure 6, the redox properties of the material increase with increasing temperature from 500 to 800 °C. The results improved with increasing x value (higher Co content). At 00°C, reproducible redox behavior was evident for all test materials, with stable As the redox temperature increased (800°C), the CaCo x Zr 1-x O 3-δ (x>0.5) showed significant CO consumption during reduction, but The O2 consumption decreased continuously with the cycle. This is because, in a high-temperature reducing atmosphere, This was thought to be due to the instability of Co (the CoO phase was released from the main phase by decomposition). 41 . When more Zr is present in the perovskite (x≦0.5), oxygen storage continues even at high temperatures. This was because the stabilized CaCo x Zr 1-x O 3-δ Perovskite The structure is formed by partially replacing Co in the B site with a certain amount of Zr (x≦0.5). This is consistent with the previously stated hypothesis that the optimal permutation can be achieved when x=0.5. The bismuth structure CaCo 0.5 Zr 0.5 O 3-δ provides optimal oxygen storage and Qualitative results were obtained.

[0127] 3.5.CaCo 0.5 Zr 0.5 O 3-δ Kinetic study of oxygen uptake by

[0128] Reduced CaCo 0.5 Zr 0.5 O 3-δ Further investigation of the oxygen uptake kinetics of perovskite Figures 7A-7C show isothermal TG data at 350-475°C and 5% O2 / He. The plot shown is used for kinetic calculations based on the above. The mixture was thoroughly degassed at 00°C and pre-reduced with 10% CO / He at the same temperature. , Hancock and Sharp 42 Solid-state kinetics research methodology summarized by Motohashi et al. 43 The analysis is based on a recent related discussion by The time-dependent fraction of (α) and its variations (ln[-ln(1-α)]) Downstream time (t), conversion time t / t 0.5 , or logarithmic scale of time (lnt) The reaction fraction (α) is calculated using equation (4) and is plotted as a function of In the middle, m0, m t , and m final are the TG measurements during the oxidation of the sample, respectively. Weight of sample at the start, weight of sample at on-stream time t (min) of TG measurement and the weight of the sample at the end of the TG measurement. The α value is allowed to have a scale of 0 to 1. , α=0 and α=1 indicate the initial and equilibrium states of the solid-state reaction, respectively.

[0129]

number

[0130] In general, the oxidation rate of the samples accelerated with increasing temperature from 350 to 475 °C. (Figure 7A), t / t 0.5 As the value increases, the slope becomes smaller. The reaction mechanism is as follows: When a linear rate evaluation equation with m is obtained, l as a function of lnt (t in minutes) This can be examined by plotting n[-ln(1-α)] (Figure 7C). The m values ​​of all linear curves are within the range of 0.6 to 1.3 (350°C, 375°C, 400°C , m = 1.29, 1.23, 1.31 at 425°C, 450°C, and 475°C, respectively. , 1.09, 0.88, 0.61).

[0131] The data points for 350°C ≤ T ≤ 475°C were well-followed by the rate equation (5) and the test The first-order kinetics of both samples under oxidation reaction conditions are shown. According to the Arrhenius equation, the oxygen uptake The reaction rate constant (k) in the logarithmic scale at the time of mixing is shown in Figure 8 as a function of the inverse temperature (100 0 / T). The reaction activation energy value (Ea , in eV) is CaCo 0.5 Zr 0.5 O 3-δ About Perovskite 0.15 It was calculated to be 9 eV.

[0132] -ln(1-α)=kt (5)

[0133] 3.6.Pd-doped CaCo x Zr 1-x O 3-δ Catalytic CO oxidation activity and catalytic HC Oxidative activity

[0134] Pd-doped CaCo 0.6-y Zr 0.4 Pd y O 3-δ (y=0, 0.05 and 0 1) Perovskite samples were used to simulate exhaust gas feed for CO oxidation and HC oxidation. The catalytic activity of the corresponding HC was investigated. C3H6 was used as a model compound for HC. Figure 9 shows the corresponding The fresh tantalum alloys had Pd contents of 5.0%, 2.5% and 0% (by weight). (a)CaCo 0.5 Zr 0.4 Pd 0.1 O 3-δ , (b) CaCo 0.55 Zr 0.4 Pd 0.05 O 3-δ and (c) CaCo 0.5 Zr 0.5 O 3-δ Catalytic oxidation of The oxidation activity is the ratio of CO and The conversion profiles were profiled as the conversion rates of C3H8 and C3H1, respectively. The 0.95, 1, and 2-phase models simulated slightly rich, stoichiometric, and lean fuel conditions. The samples were collected at three different stoichiometric numbers (SN), .07 and 1.16. As can be seen, All perovskite-type OSMs exhibited excellent catalytic activity for CO oxidation and HC (C3H6) oxidation. The complete conversion of CO and HC was observed at 350 The T of CO oxidation was observed at temperatures below 100°C. 50 While the temperature is low at 240℃, T of 50 The reaction temperature was as low as 250°C. All the Pd-doped CaCo x Zr 1-x O 3-δ three The HC oxidation activity of the two-way catalyst (TWC) is not higher than that of the most advanced three-way catalyst (TWC). These encouraging data support the proposed perovskite three-way catalyst (T This clearly demonstrates the excellent potential of the WC.

[0135] In general, Pd-doped CaCo x Zr 1-x O 3-δ The samples were Especially at higher SN (fuel lean) conditions, the catalytic oxidation activity was higher than that of the Pd-free sample. The presence of Pd enhanced the surface chemisorption of CO and C3H8 molecules, and It is clear that the dissociation / activation of CaCo is promoted by the oxidation activity. 0.5 Zr 0. 4Pd 0.1 O 3-δ and CaCo 0.55 Zr 0.4 Pd 0.05 O 3-δ At the same level as This suggests that mass transport limitations existed in the latter sample under the test conditions. A higher conversion rate was observed under richer conditions (SN=0.95) and under reducing conditions. This is due to the more accessible active sites generated by the "segregation of Pd to the surface." Most likely to 27,29,36 Pd-free CaCo x Zr 1-x O 3-δ too It shows CO conversion and C3H8 conversion when less O2 is present in the feed (dilute In the absence of Pd, surface chemisorption is the rate-limiting step. At the same time, CO and C3H8 from the atmosphere are transported from the newly generated surface oxygen or lattice It was highly likely that the oxygen on the surface moved directly to the fuel, and that the oxidation occurred in the fuel-rich condition. (SN=0.95), all samples showed a decrease in CO conversion and H It is interesting to note that the amount of 2 produced is increased at higher temperatures, which is thermodynamically favorable (endothermic reaction). ) Steam reforming reaction (excess C3H8 reacts with the H2O product from the oxidation reaction to produce H2 and This suggests that the generation of CO is caused by the stoichiometric engine mode. This could have been avoided by

[0136] 4. Conclusion

[0137] In this disclosure, CaCo x Zr 1-x O 3-δ (x=0, 0.3, 0.5, 0.7 and 0.9) Perovskite was synthesized for the first time, and state-of-the-art perovskite and ceria-based oxygen Improved redox properties and oxygen storage capacity (OSC) compared to O2 storage materials (OSM) It has been reported that Pd-doped CaCo 0.6-yZr 0.4 Pd y O3(y=0. 0.5, 0.1 and 0.2) samples were tested for the oxidation of C3H6 and CO under simulated exhaust conditions. The catalysts showed promising catalytic activity, suggesting their potential use in three-way catalysts for automotive emissions control. Ta.

[0138] The perovskites examined have the orthorhombic Lakargiite CaZrO3 structure. The partial substitution of Co by Zr at the B site results in a perovskite The crystallinity of the structure is improved, but the impurity of the ZrO phase increases with increasing Zr content. For the Pd-containing samples, Pd is bulk Pd 2+ and surface Pd 0 It exists in both forms. , surface Pd 0 The amount of increased with increasing Pd content. When x was around 0.5, Perovskites exhibit optimal crystallinity and minimal impurities.

[0139] The redox and OSC properties were mainly attributed to Co and Pd in ​​the B sites. The partial substitution by promoted the reduction of Co species by lowering the reduction temperature, but The amount of increased with increasing Co content. The Pd dopant also promoted the reduction of Co, and the catalytic The reducibility of CaCo with or without Pd doping was improved. 0.5 Zr 0.5 Perovskite-type OSMs with the composition O3 have optimized reducibility and structural stability. Further kinetic studies were performed on CaCo 0.5 Zr 0.5 O 3-δ About 0.1 A first-order reaction mechanism with an activation energy (Ea) of 59 eV was demonstrated.

[0140] Fresh CaCo 0.5 Zr 0.4 Pd 0.1 O 3-δ , CaCo 0.55 Zr0 .4 Pd 0.05 O 3-δ and CaCo 0.5 Zr 0.5 O 3-δ All samples were burned. From fuel-lean to fuel-rich conditions (SN = 1.16, 1.07 and 0.95), The catalytic oxidation showed significant conversion of C3H6 and CO, and the most important conversion of C3H6 and CO was Low T 50 The Pd-doped perovskite exhibited excellent thermal stability under all three conditions. In particular, under higher SN conditions, the Pd-free perovskite The oxidation activity was high. For the same Pd-containing sample, the conversion was higher under richer conditions ( This is consistent with the reported phenomenon of "Pd segregation to the surface." This may be due to elephants. 7.References (1) Royer, S.; Alamdari, H.; Duprez, D.; Kaliaguine, S. Appl. Catal. B Environ. 2005, 58 (3-4), 273-288. (2) Klimkowicz, A.; Swierczek, K.; Takas aki, A.; Dabrowski, B. Solid State Ion. 2014, 257, 23-28. (3) Hernandez, WY; Tsampas, MN; Zh ao, C.; Boreave, A.; Bosselet, F.; Verno ux, P. Catal. Today 2015, 258, Part 2, 5 25-534. (4) Mizusaki, J.; Worker, H.; Naraya, K. ; Sasamoto, T. Solid State Ion. 1991, 49 , 111-118. (5) Albrecht, KJ; Jackson, GS; Bra and, RJ Appl. Energy 2016, 165, 285-29 6. (6) Galvez, ME; Jacot, R.; Scheffe, J .; Cooper, T.; Patzke, G.; Steinfeld, A. Phys. Chem. Chem. Phys. 2015, 17 (9), 6 629-6634. (7) Babiniec, SM; Joker, EN; Mille r, JE; Ambrosini, A. Sol. Energy 2015 , 118, 451-459. (8) McDaniel, AH; Ambrosini, A.; Coke conduct; Miller, JE; Chueh, WC; THEIR 'Hayre, R.; Tong, J. Energy Procedia 201 4, 49, 2009-2018. (9) Demont, A.; Abanades, S. RSC Adv. 20 14, 4 (97), 54885-54891. (10) Zheng, Q.; Farrauto, R.; Deeba, M. Catalysts 2015, 5 (4), 1797-1814.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> (11) Zheng, Q.; Farrauto, R.; Deeba, M.;<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> Valsamakis, I. Catalysts 2015, 5 (4), 1<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> 770-1796.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> (12) Simson, A.; Roark, K.; Farrauto, R.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> Appl. Catal. BEnviron. 2014, 158-159,<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> 106-111.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> (13) Ran, R.; Wu, X.; Weng, D.; Fan, J.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> J. Alloys Compd. 2013, 577, 288-294.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> (14) Keav, S.; Matam, SK; Ferri, D.;<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> Weidenkaff, A. Catalysts 2014, 4 (3), 22<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> 6-255.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> (15) Levasseur, B.; Kaliaguine, S. Appl.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> Catal. BEnviron. 2009, 88 (3-4), 305-3<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> 14.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> (16) Guilhaume, N.; Primet, M. J. Catal.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> 1997, 165 (2), 197-204.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> (17) Uenishi, M.; Tanaka, H.; Taniguchi,<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> M.; Tan, I.; Sakamoto, Y.; Matsunaga, S<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> .; Yokota, K.; Kobayashi, T. Appl. Catal<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> . Gen. 2005, 296 (1), 114-119.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> (18) Tanaka, H.; Taniguchi, M.; Uenishi,<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> M.; Kajita, N.; Tan, I.; Nishihata, Y.; Mizuki, J. 'chiro; Narita, K.; Kimura, M.; Kaneko, K. Angew. Chem. Int. Ed. 20 06, 45 (36), 5998-6002. (19) You, R.; Zhang, Y.; Liu, D.; Mother, M.; Zheng, L.; Zhang, J.; Hu, TJ Phys . Chem. C 2014, 118 (44), 25403-25420. (20) Nishihata, Y.; Mizuki, J.; Akao, T. ; Tanaka, H.; Winnie, M.; Kimura, M.; O Camoto, T.; Hamada, N. Nature 2002, 418 (6894), 164-167. (21) Glicente, A.; Pacella, M.; Guiot, M.; I said, MM; Canu, P. Appl. Catalys . B Environ. 2016, 180, 94-105. (22) Li, Z.; Meng, M.; Zha, Y.; Dai, F.; Hu, T.; Xie, Y.; Zhang, J. Appl. Catalog. B Environ. 2012, 121–122, 65–74. (23) Shen, S.-T.; Weng, H.-S. Ind. Eng. Chem. Res. 1998, 37 (7), 2654-2661. (24) Tanaka, H.; Mizuno, N.; Missions, M. Appl. Catalog. City. 2003, 244 (2), 371-382 . (25) Tanaka, H.; Fashions, M. Curr. Open. Solid State Mater. Sci. 2001, 5(5), -387. (26) Tanaka, H.; Tan, I.; Uenishi , M. ; K imura, M.; Dohmae, K. Top. Catalog. 2001, 16-17 (1-4), 63-7 (27) Lee, X.; Chen , C. ; Liu , C. ; Xian, H. (1999). ; Guo, L.; Lv, J.; Jiang, Z.; Vernoux, P. (1999). . . . . ACS Catalog. 2013, 3(6), 1071–1 (28) Yoon, DY; Kim , YJ ; Lim, JH ; Cho, BK; Hong, SB; Nam, I.-S.; C houng, JWJ Catalog. Rev. 2015, 330, 71–83. (29) Malamis, SA; Harrington , RJ ; Katz , MB ; Koerschner , DS ; Zhang, S. (1999). .; Cheng, Y.; Xu, L.; Jen, H.-W.; McCabe , RW; Graham , GW ; Pan, X. Catalog. T oday 2015, 258, Part 2, 535-542. (30) H. Bork, A.; Kubicek , M. ; Struzik, M.; M. Rupp, JLJ Mater. Chem. A 201 5, 3(30), 15546–15557. (31) Miura, N.; Ikeda, H.; Tsuchida, A. Ind. Eng. Chem. Res. 2016, 55 (11), 3091 -3096. (32) Mota, N.; Barrio, L.; Alvarez-Galva n, C.; Fauth, F.; Navarro, R.M.; Fierro , JLGJ Phys. Chem. C 2015, 119 (2 9), 16708-16723. (33) Ikeda, H.; Tsuchida, A.; Morita, J. ; Miura, N. Ind. Eng. Chem. Res. 2016, 5 5 (22), 6501-6505. (34) Dey, S.; Naidu, B.S.; Govindaraj, TO.; Rao, CNR Phys. Chem. Chem. Phys . 2014, 17 (1), 122-125. (35) Pecchi, G.; Reyes, P.; Zamora, R.; Campos, C.; Cadus, L.E.; Barbero, B.P Catal. Today 2008, 133-135, 420-427. (36) Sartipi, S.; Khodadadi, A.A.; Mort azavi, Y. Appl. Catal. B Environ. 2008, 83 (3-4), 214-220. (37) Escalona, ​​N.; Fuentealba, S.; Sin i, G. Appl. Catal. Jan. 2010, 381 (1-2), 253-260. (38) Shen, W.-J.; Okumura, M.; Matsumura , Y.; Haruta, M. Appl. Catal. Gen. 2001, 213(2), 225-232. (39) Song, H.; Ozkan, USJ Phys. Che m.A 2010, 114 (11), 3796-3801. (40) Mamontov, E.; Egami, T.; Brezny, R. ; Koranne, M.; Tyagi, SJ Phys. Chem. B 2000, 104 (47), 11110-11116. (41) Hu, L.; Zhou, C.; Wu, C.; Zhou, S.; Wang, WG; Yin, H. Eur. J. Inorg. Che m. 2015, 2015 (13), 2317-2322. (42) Hancock, JD; Sharp, JHJ Am. Ceram. Soc. 1972, 55 (2), 74-77. (43) Motohashi, T.; Ueda, T.; Masubuchi, Y.; Kikkawa, SJ Phys. Chem. C 2013, 117(24), 12560-12566.

[0141] It is understood that the above description represents only exemplary embodiments and examples. For the convenience of the reader, the above description is limited to a limited number of all possible embodiments. We have focused on representative examples, examples that teach the principles of the present disclosure. It is not intended to exhaustively list all possible variations or even combinations of those variations described. Alternative embodiments may not be presented for any particular portion of this disclosure. or further undescribed alternative embodiments are available. The possibility of such an embodiment should not be considered as a disclaimer of those alternative embodiments. Many of these undescribed embodiments are not intended to be limiting, rather than being merely illustrative of the application of the principles of this disclosure. Rather, it will be understood to include differences in techniques and materials. shall be limited to no greater than that set forth in the following claims and equivalents thereto. This is not intended to be.

[0142] Incorporation by Reference

[0143] All references, articles, publications, patents, patent publications, and patent applications cited herein are the property of their respective owners. This application is incorporated by reference in its entirety for all purposes. Any references, articles, publications, patents, patent publications, and patent applications cited herein References to the invention in any form that constitute valid prior art or that are part of the common general knowledge are also In any country in the world, as an admission or any indication of the formation of Although the present disclosure has been described in conjunction with its detailed description, the foregoing description It should be understood that the above is for illustrative purposes and is not limiting in scope. Aspects, advantages, and modifications are within the scope of the following claims. All publications, patents, and patent applications cited are hereby incorporated by reference as if they were each individually incorporated by reference. The referenced patent applications are incorporated by reference as if each such application was specifically and individually indicated to be incorporated by reference. No. 6,399,433, which is incorporated herein by reference.

Claims

1. A platinum group metal, Formula CaCo 1-x Zr x O 3-δ (In the above formula, x is 0.02≦x≦0.98, where δ is a number defined by 0.0≦δ≦1.0 A catalyst comprising a perovskite.

2. 2. The method of claim 1, wherein the platinum group metal is Pd, Pt, Rh, Ru, or a combination thereof. The catalyst according to claim 1.

3. 2. The catalyst of claim 1, wherein the platinum group metal is a combination of Pd and Rh.

4. A 2 O 3 Support, titania support, zirconia support, ceria support, silica support, alumina - any of claims 1 to 3 on a silica, zeolite or carbon support The catalyst according to any one of claims 1 to 5.

5. The catalyst according to any one of claims 1 to 3, which is formed in the form of a monolith honeycomb block. 。

6. The method according to any one of claims 1 to 3, wherein the method is coated on a ceramic monolith honeycomb block. Catalyst on board.

7. 7. The ceramic monolith honeycomb block of claim 6, wherein the ceramic monolith honeycomb block is a cordierite compound. The catalyst according to claim 1.

8. The catalyst according to any one of claims 1 to 7, which is a three-way catalyst.

9. NO from internal combustion engines x or reduction of carbon monoxide or hydrocarbon acids from internal combustion engines. The catalyst according to any one of claims 1 to 8, which is used to catalyze the polymerization of

10. 10. The catalyst of claim 9, wherein the internal combustion engine is an automobile engine.

11. The catalyst of claim 9 , wherein the internal combustion engine is operated under stoichiometric conditions.

12. The internal combustion engine is configured to use diesel fuel, ethanol / gasoline hybrid fuel, gasoline The catalyst according to claim 9, wherein the fuel is natural gas.

13. The ethanol / gasoline hybrid fuel is 85% ethanol / 15% gasoline ( E85).

14. 1. A method for reducing emissions from an internal combustion engine, comprising: contacting the exhaust stream from the internal combustion engine with a catalyst; The catalyst comprises a platinum group metal and a catalyst of the formula CaCo 1-x Zr x O 3-δ (In the above formula, x is 0. x is a number defined by 0.2≦x≦0.98, and δ is a number defined by 0.0≦δ≦1.

0. and a perovskite having a ZnO content of 0.1 to 0.25 wt %, wherein the ZnO content is 0.1 to 0.25 wt %, and

15. 14. The platinum group metal of claim 13, wherein the platinum group metal is Pd, Pt, Rh, Ru, or a mixture thereof. The method described above.

16. The catalyst is Al 2 O 3 The method of claim 14 or 15, which is on a carrier.

17. 17. The internal combustion engine according to claim 14, wherein the internal combustion engine is operated under stoichiometric air-fuel ratio conditions. How to.

18. The internal combustion engine is configured to use diesel fuel, ethanol / gasoline hybrid fuel, gasoline The method according to any one of claims 14 to 17, wherein the fuel is natural gas.

19. 1. An exhaust system for reducing emissions from an internal combustion engine, comprising: A platinum group metal and a compound of the formula CaCo 1-x Zr x O 3-δ (In the above formula, x is 0.02≦x≦0 .98, and δ is a number defined by 0.0≦δ≦1.

0. a catalyst comprising a perovskite having a and a solid support.

20. Formula CaCo 1-x Zr x O 3-δ (In the above formula, x is 0.02≦x≦0.98, where δ is a number defined by 0.0≦δ≦1.0 , perovskite catalysts.

21. 21. The catalyst of claim 20, wherein x is a number defined by 0.2≦x≦0.

8. 。

22. 20. The method according to claim 20, wherein the compound is in the form of particles having a diameter of more than about 1.0 nm and less than about 10 mm. Catalyst according to 1.

23. 23. The catalyst of claim 22, wherein the particles have a diameter greater than about 1.0 μm and less than about 50 μm. 。

24. Formula CaCo 1-x Zr x O 3-δ (In the above formula, x is 0.02≦x≦0.98, where δ is a number defined by 0.0≦δ≦1.0 A method for producing a perovskite catalyst, comprising the steps of: (a) dissolving salts of Ca, Co and Zr to form a homogeneous solution; (b) drying the solution; and (c) forming a perovskite catalyst by calcination and sintering.

25. The firing is performed at about 300° C. to about 500° C., and the sintering is performed at about 800° C. to about 140° C.

25. The method of claim 24, wherein the method is carried out at 0°C.

26. 1. A method for producing hydrogen by thermochemical water splitting, comprising: (a) releasing oxygen to produce an oxygen-deficient perovskite catalyst by the addition of a compound of the formula CaCo 1 -x Zr x O 3-δ (In the above formula, x is a number defined by 0.02≦x≦0.98.) where δ is a number defined by 0.0≦δ≦1.

0. heating the medium; and (b) releasing hydrogen to regenerate the perovskite catalyst by removing the oxygen-deficient perovskite. A method comprising contacting particles of a baskite catalyst with water.

27. 27. The method of claim 26, wherein the hydrogen is produced in a fluidized bed reactor.

28. The fluidized bed reactor is a circulating fluidized bed reactor, a bubbling fluidized bed reactor, a transport reactor or a chemical 28. The method of claim 27, which is a chemical loop reactor.

29. 27. The method of claim 26, wherein the hydrogen is produced in a fixed bed reactor.

30. 2. The method of claim 1, wherein the perovskite catalyst is heated to a temperature of about 400° C. to about 1000° C.

30. The method according to any one of claims 6 to 29.

31. The hydrogen produced in the next reactor is used to reduce carbon dioxide to carbon monoxide and water. The method of any of claims 26 to 30, further comprising using.

32. Carbon dioxide or carbon monoxide is generated in the next reactor to reduce it to hydrocarbons and water. The method of any one of claims 21 to 26, further comprising using the hydrogen produced.

33. To reduce carbon dioxide or carbon monoxide to alkanes or alkenes and water, 27. The method according to claim 21, further comprising using hydrogen produced in the reactor. Method of posting.

34. To produce aldehydes from a mixture of carbon monoxide and alkenes, the following reactor is used: The method of any of claims 21 to 26, further comprising using the hydrogen produced.

35. To improve the quality of crude oil, heavy petroleum or biomass oil feedstocks, The hydrogen produced in the next reactor is used for hydrotreating or hydroprocessing. The method of any of claims 21 to 26, further comprising:

36. 32. The method of claim 31 , wherein the carbon dioxide is produced in a chemical looping combustion fuel reactor. Law.

37. 1. A method for reducing carbon dioxide to carbon monoxide, comprising the steps of: (a) releasing oxygen and producing an oxygen-deficient perovskite catalyst by the addition of a compound of the formula CaCo 1- x Zr x O 3-δ (In the above formula, x is a number defined by 0.02≦x≦0.98.) where δ is a number defined by 0.0≦δ≦1.

0. heating the medium; and (b) removing oxygen, releasing carbon monoxide, and regenerating the perovskite catalyst; contacting the oxygen deficient perovskite catalyst with carbon dioxide to produce a carbon dioxide gas.

38. 1. A system for thermocatalytically splitting water to produce hydrogen, comprising: (a) forming an oxygen-deficient perovskite catalyst and releasing oxygen by reacting with a compound of the formula CaCo 1-x Zr x O 3-δ (In the above formula, x is a number defined by 0.02≦x≦0.98.) where δ is a number defined by 0.0≦δ≦1.

0. an oxygen generating reactor for heating the catalyst; (b) reacting the oxygen-deficient perovskite catalyst with water vapor and forming a hydrogen-containing perovskite catalyst; a hydrogen generation reactor for regenerating the catalyst and producing hydrogen; and (c) returning the regenerated perovskite catalyst to the oxygen generation reactor. A system comprising a device.

39. 40. The system of claim 38, wherein the oxygen generation reactor is a fluidized bed reactor.

40. 40. The system of claim 38 or 39, wherein the hydrogen generation reactor is a fluidized bed reactor.

41. 40. The system of claim 38, wherein the hydrogen generating fluidized reactor bed is a riser reactor.

42. Either the oxygen generation reactor or the hydrogen generation reactor is a fixed bed reactor. The method of claim 38.

43. The hydrogen is used to reduce carbon dioxide in exhaust gases from a combustion process. A system according to any one of claims 38 to 42.

44. 43. The method according to claim 38, wherein the hydrogen is used for thermal energy storage. The system is as follows:

45. Providing energy for the water splitting reaction while minimizing energy loss. The method according to any one of claims 38 to 44, which is integrated into a chemical manufacturing system and a chemical manufacturing facility. The system is as follows:

46. A platinum group metal and a metal of the formula (La 1-y Ca y ) 1-x Mn x O 3-δ , La 1-x (Co 1- y R y ) x O 3-δ 、 1-y Sr y ) 1-x Co x O 3-δ 、Sr 1-x (Co 1-y Fe y ) x O 3-δ , (Sr 1-y Ca y ) 1-x Fe x O 3-δ (In the above formula, x is a number defined by 0.02≦x≦0.98, and y is a number defined by 0.02≦y≦0.9 8, and δ is a number defined by 0.0≦δ≦1.

0. and a perovskite having the above structure.

47. 47. The method of claim 46, wherein y is a number defined by 0.15≦y≦0.

85. catalyst.

48. 48. The method according to claim 46 or 47, wherein x is a number defined by 0.3≦x≦0.

7. The catalyst described herein.

49. 5. The method of claim 4, wherein the platinum group metal is Pd, Pt, Rh, Ru, or a mixture thereof.

6. The catalyst according to any one of claims 6 to 48.

50. 50. The catalyst of claim 49, wherein the platinum group metal is a mixture of Pd and Rh.

51. A 2 O 3 Support, titania support, zirconia support, ceria support, silica support, alumina - on a silica support, a zeolite support or a carbon support. The catalyst according to any one of the preceding claims.

52. The honeycomb block according to any one of claims 46 to 50, which is formed in the form of a monolithic honeycomb block. catalyst.

53. Any of claims 46 to 50, which is coated on a ceramic monolith honeycomb block. The catalyst according to claim 1.

54. 6. The ceramic monolith honeycomb block of claim 5, wherein the ceramic monolith honeycomb block is a cordierite compound. Catalyst according to claim 3.

55. The catalyst according to any one of claims 46 to 54, which is a three-way catalyst.

56. NO from internal combustion engines x or reduction of carbon monoxide or hydrocarbon acids from internal combustion engines. The catalyst according to any one of claims 46 to 55, which is used to catalyze the polymerization of

57. 57. The catalyst of claim 56, wherein the internal combustion engine is an automobile engine.

58. 1. A method for reducing emissions from an internal combustion engine, comprising: contacting the exhaust stream from the internal combustion engine with a catalyst; The catalyst comprises a platinum group metal and a metal of the formula (La 1-y Ca y ) 1-x Mn x O 3-δ , La 1- x (Co 1-y R y ) x O 3-δ 、 1-y Sr y ) 1-x Co x O 3-δ 、Sr 1-x (Co 1-y Fe y ) x O 3-δ 、(Sr 1-y Ca y ) 1-x Fe x O 3-δ ( In the above formula, x is a number defined by 0.02≦x≦0.98, and y is 0.02 ≦y≦0.98, and δ is defined by 0.0≦δ≦1.

0. and a perovskite having a ZnO content of 0.1 to 0.25,

59. 1. An exhaust system for reducing emissions from an internal combustion engine, comprising: A platinum group metal and a metal of the formula (La 1-y Ca y ) 1-x Mn x O 3-δ , La 1-x (Co 1- y R y ) x O 3-δ 、 1-y Sr y ) 1-x Co x O 3-δ 、Sr 1-x (Co 1-y Fe y ) x O 3-δ , (Sr 1-y Ca y ) 1-x Fe x O 3-δ (In the above formula, x is a number defined by 0.02≦x≦0.98, and y is a number defined by 0.02≦y≦0.9 8, and δ is a number defined by 0.0≦δ≦1.

0. a catalyst comprising a perovskite having a and a solid support.

Citation Information

Patent Citations

  • Catalyst for decomposing NOX

    JP1992118050A

  • Redox material for thermochemical water splitting, and method for producing hydrogen

    US20110300064A1

  • Redox material for thermochemical water decomposition and method for producing hydrogen

    WO2013021506A1

  • Catalyst for manufacturing thermochemical fuel, and method for manufacturing thermochemical fuel

    WO2013141385A1